Design and Construction of a Satay Grill Based on Thermoelectric Generator as a Source of Electrical Energy - Nulhakim, Lukman; Syafrizal; Tauvana, Ade Irvan; Widodo; Nurhidayatuloh, Farhan (Piston: Journal of Technical Engineering, 2025)
Thermoelectric Generator is a technology used to generate electrical energy by utilizing the Seebeck effect, which occurs due to the temperature difference between the hot and cold sides. This study aims to determine the voltage generated by the thermoelectric generator from the process of burning satay using coconut shell charcoal. In this experiment, 6 pieces of thermoelectric generator type TEG1-241-1. 4-1. 2 were used which were connected in series. The pieces were mounted on aluminum material measuring 165 x 110 x 15 mm, and equipped with a heatsink at the bottom of the satay grill body for cooling. The heatsink used is an extrude model. Testing began when the charcoal had reached a red color. The maximum voltage generated reached 2,25 V in seven minutes, with a temperature difference reaching 5,9 °C. The temperature on the hot side was recorded at 102,2 °C, while on the cold side it was 96,3 °C.